2016
DOI: 10.2118/173354-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fully Coupled Hydromechanical Simulation of Hydraulic Fracturing in 3D Discrete-Fracture Networks

Abstract: We developed a hydraulic-fracturing simulator that implicitly couples fluid flow with the stresses induced by fracture deformation in large, complex, 3D discrete-fracture networks (DFNs). The code is efficient enough to perform field-scale simulations of hydraulic fracturing in DFNs containing thousands of fractures, without relying on distributed-memory parallelization. The simulator can describe propagation of hydraulic fractures and opening and shear stimulation of natural fractures. Fracture elements can o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(42 citation statements)
references
References 72 publications
1
40
0
1
Order By: Relevance
“…In addition, this work studied 2‐D fracture system, and there could be important 3‐D effects. While several studies have investigated fluid flow in stressed 3‐D fracture networks (Garipov et al, ; Lei et al, ; McClure et al, ), the effects of geological stress on tracer transport through 3‐D fracture networks remain to be investigated. A recent study has shown that the Bernoulli CTRW model can capture particle transport through 3‐D fracture networks (Hyman et al, ), and the natural extension of this study will be the effects of geological stress on particle transport through stressed 3‐D fracture networks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this work studied 2‐D fracture system, and there could be important 3‐D effects. While several studies have investigated fluid flow in stressed 3‐D fracture networks (Garipov et al, ; Lei et al, ; McClure et al, ), the effects of geological stress on tracer transport through 3‐D fracture networks remain to be investigated. A recent study has shown that the Bernoulli CTRW model can capture particle transport through 3‐D fracture networks (Hyman et al, ), and the natural extension of this study will be the effects of geological stress on particle transport through stressed 3‐D fracture networks.…”
Section: Discussionmentioning
confidence: 99%
“…In all of our computational results, the length of the phase-field diffusive zone is set to be = 2h min and so the initial thickness of phase-field variable is 2h min , where h min is the minimum mesh size. In addition, we set the regularization parameter as = 10 −10 × h min , and the parameter defined in (16) as D = 0.5. Except the last example using a field data in Section 4.6, we assume homogeneous and isotropic reservoir domains, and the following parameters are consistently used: K R = 1.0 × 10 −12 m 2 , R = F = 1 cp, and c F = 4.0 × 10 −10 Pa −1 .…”
Section: Numerical Examplesmentioning
confidence: 99%
“…5 However, modeling fluid-driven fracturing processes in porous media is challenging because of its complexity involving solid-fluid interaction and various fracture geometry scenarios. There have been a lot of studies to model the fracturing process by using cohesive (interface) elements, [6][7][8][9] extended finite element method (XFEM)/generalized finite element method (GFEM)/partition of unity method (PUM), 8,[10][11][12] displacement discontinuity methods, [13][14][15][16] peridynamics, 17 and others.…”
Section: Introductionmentioning
confidence: 99%
“…The next sections present the numerical studies performed by using three benchmark solutions. These are the solutions to (i) the Khristianovic-Geertsma-de Klerk problem (KGD problem) [5,6,17], given, e.g., in the papers [7,8]); (ii) the axisymmetric problem [9,10]; and (iii) the truly 3D problem for a pay-layer between half spaces with symmetric stress contrast [11,18]. The numerical results show that the method avoiding explicit evaluation of the normal may be used in practical calculations.…”
Section: Introductionmentioning
confidence: 99%